Upaya Guru Bimbingan Konseling Dalam Mengatasi Perilaku Bullying Siswa di UPTD SMP Negeri 1 Mendo Barat - Nimala, Cica; Anisa, Anisa (Program Studi Bimbingan dan Konseling Pendidikan Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This research was motivated by the widespread problems of negative student behavior in the school environment, such as bullying between students and acts of physical violence such as hitting, pushing, and pinching. All of these behaviors fall into the category of bullying. The objectives of this research are 1) Describe the bullying behavior of students at UPTD SMP Negeri 1 Mendo Barat. 2) Describe the efforts of the Counseling Guidance teacher in overcoming student bullying behavior at UPTD SMP Negeri 1 Mendo Barat. 3) Describe the obstacles felt by Guidance Counseling teachers in dealing with bullying study the theory used by Olweus. The method used in this research is a qualitative descriptive approach. The results of the research show that 1) the form of bullying that occurs is verbal in the form of making fun of skin color, weight, or other physical appearance. Physical bullying takes the form of pushing, hitting, kicking, disturbing friends who are studying, and pulling each other's hair. 2) Guidance Counseling Teachers introduce classical and non-classical programs as prevention and intervention efforts. 3) Obstacles in overcoming bullying include lack of support from the school, sufficient knowledge and expertise, and limited time and teachers resources which are the main obstacles for guidance and counseling teachers